The Effect Of Environmental, Social, And Governance (ESG) Disclosure And Intellectual Capital On Firm Value Moderated By Managerial Ownership - Joseline, Joseline; Sriwati, Sriwati (UNIVED Press, 2026)
This study analyzes the effect of Environmental, Social, and Governance (ESG) disclosure and intellectual capital on firm value, with managerial ownership as a moderating variable. The sample consists of 40 energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period, selected using purposive sampling based on the availability of sustainability and annual reports. The data were analyzed using panel data regression with EViews 12 software. The results show that ESG disclosure has no significant effect on firm value, while intellectual capital has a positive and significant effect. Managerial ownership weakens the influence of ESG disclosure and intellectual capital on firm value. These findings indicate that managerial ownership has not been able to enhance the effectiveness of these factors in creating firm value.